EFEK KUALITAS PELAPORAN KEUANGAN DAN KONSERVATISME AKUNTANSI TERHADAP EFISIENSI INVESTASI PADA PERUSAHAAN SEKTOR PROPERTIES DAN REAL ESTATE DI BEI - Yubiharto, Yubiharto; Murdijaningsih, Tjahjani (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2025)
Abstract This study aims to examine the effect of financial reporting quality and accounting conservatism on investment efficiency. The study period was 2019-2023, with a sample of 30 property and real estate companies listed on the Indonesia Stock Exchange, with a total of 150 observations. Purposive sampling was used for sampling. Panel data regression analysis was used for analysis. The study found that financial reporting quality had no positive effect on investment efficiency. Meanwhile, accounting conservatism had a positive effect on investment efficiency. The implication of this study is that managers must apply accounting conservatism principles when presenting financial reports to send a positive signal to investors. This conservatism principle can provide protection against investor and creditor claims.